Tears of joy, aesthetic chills and heartwarming feelings: Physiological correlates of Kama Muta. (12th August 2020) - Zickfeld, Janis H.; Arriaga, Patrícia; Santos, Sara Vilar; Schubert, Thomas W.; Seibt, Beate
Abstract: Situations involving increased closeness or exceptional kindness are often labeled as moving or touching and individuals often report bodily symptoms, including tears, goosebumps, and warmth in the body. Recently, the kama muta framework has been proposed as a cross‐cultural conceptualization of these experiences. Prior research on kama muta has mostly relied on subjective reports. Thus, our main goal of the present project was to examine the pattern of physiological responses to kama muta inducing videos and compare it to the patterns for the similar, though distinct emotions of sadness and awe . One hundred forty‐four Portuguese and Norwegian participants were individually exposed to all three emotion conditions. Several psychophysiological indexes of the autonomic nervous system were collected continuously during exposure, including cardiovascular, respiratory, and electrodermal activity, facial EMG, skin temperature, as well as piloerection and lachrymation using cameras. Overall, the results partly replicated previous findings on being moved experiences and self‐report studies. Strong self‐reported experiences of kama muta were associated with increased phasic skin conductance, skin temperature, piloerection, and zygomaticus activity, while they were associated with reduced heart rate, respiration rate, and tonic skin conductance. The physiological profile of kama muta was successfully distinguished from sadness and awe, partly corroborating self‐report evidence. We obtained no clear evidence of a kama muta association with the occurrence of lachrymation or heart rate variability. Our findings provide a systematic overview of psychophysiological response to experiences of kama muta, and help to inform future research on this emotion and positive emotions in general. Abstract : The heartwarming emotion of kama muta is experienced consistently across several cultural contexts. In the present contribution we provide the first comprehensive test of its psychophysiological correlates and profile, and compare it with other emotions. Our findings complement previous findings on psychophysiology of being moved, but also provide novel insights into autonomic nervous system responses of kama muta and positive emotions in general.